APPLICATION OF CATEGORIES OF THE INTERNATIONAL CLASSIFICATION OF FUNCTIONING IN THE ORGANIZATION OF MEDICAL REHABILITATION OF PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - V. V. Afanasyeva; A. A. Potapchuk (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
The article is devoted to an actual problem-the choice of categories of the International classification of functioning in the medical rehabilitation of patients with chronic obstructive pulmonary disease. An analytical review of the Russian and foreign literature was conducted, the categories of ICF included in the complex and brief set of ICF for obstructive pulmonary diseases, recommended by WHO in work with patients with COPD were carefully studied, which showed the relevance of the problem, unsolved problems and prospects for research on this topic.